Why Aren't Advanced High–Strength Steels More Widely Used?: Stakeholder Preferences and Perceived Barriers to New Materials. (24th November 2014) - Alriksson, Stina; Henningsson, Marianne
Summary Advanced high‐strength steels may reduce the use of nonrenewable resources and energy given that the amount of material needed is smaller, compared to traditional steel grades. Still, advanced steel grades are not utilized to the extent that could be expected. This study examines stakeholders' preferences of steel characteristics and perceived barriers to the introduction of new materials. Focus group interviews were used to identify steel characteristics and perceived barriers. Stakeholder preferences of steel characteristics were evaluated through a conjoint analysis; the results showed that low weight was given the highest priority, followed by high impact strength and low price. Low chromium content was the steel characteristic of least interest. Perceived barriers to the introduction of high‐strength steel were categorized as technical barriers, knowledge barriers, scrap management barriers, suitability barriers, and cost barriers.